Indonesian contract law in practice and its relevance to the development of mortgage contract law bank loans - Richard, Richard (Institute for Law and Economics Studies, 2025)
This study aims to examine the application of Indonesian contract law in bank loan agreements involving collateral rights and to evaluate its relevance to the development of modern mortgage contract law. Using an empirical juridical approach supported by both library research and field data, this research analyzes how the fundamental principles of contract law—such as freedom of contract, good faith, balance, and legal certainty—are implemented in banking practices. The findings indicate that contract law provides a legal foundation for regulating reciprocal obligations between creditors and debtors, primarily through instruments such as the Power of Attorney to Impose Security Rights (SKMHT) and the Deed of Grant of Security Rights (APHT). The enactment of Law No. 4 of 1996 on Mortgage Rights strengthens creditor protection by introducing a more enforceable and simplified collateral mechanism. However, several obstacles remain, including debtor default, administrative deficiencies, legal uncertainty in collateral execution, and imbalanced standard contracts that often disadvantage debtors. The study concludes that Indonesian contract law plays a strategic role in ensuring legitimacy, legal certainty, and balanced protection for both creditors and debtors, although continuous regulatory refinement and enforcement improvement are necessary to address existing challenges and align with socio-economic developments in the banking sector.